Multiple inversions of Rayleigh wave dispersion curve for geotechnical site characterization using particle swarm optimization dan genetic algorithm - Wirawan, Rezki; Safani, Jamhir; Rubaiyn, Al (Journal of Physics: Theories and Applications, 2023)
The inversion of the Rayleigh wave dispersion curve is a crucial step in the multi-channel analysis of surface waves (MASW) method, used to obtain the shear wave velocity (Vs) profile. The nonlinear and multimodal nature of the dispersion curve makes a global optimization approach, such as particle swarm optimization (PSO) and genetic algorithm (GA), the optimal choice for inversion. This study aims to compare the performance of multiple inversions of PSO (MI-PSO) and multiple inversions of GA (MI-GA) in solving the inversion problem of the Rayleigh wave dispersion curve. The test results indicate that the utilized MI-PSO outperforms MI-GA in terms of computational time and accuracy of the obtained model